PENEGAKAN PENGAWASAN DALAM MELINDUNGI KONSUMEN TERHADAP TRANSPORTASI ONLINE DI INDONESIA: A. PENDAHULUAN - Virgy, Rery Lasinta; SETIAWAN, ANDRY (Jurnal Media Justitia Nusantara, 2025)
Online transportation is growing rapidly due to technological advances, this makes it easier for consumers to use it and can be quickly and easily accessed to meet the needs desired by consumers. There are positive and negative impacts that require supervision to minimize negative impacts. This study aims to find out and also analyze the enforcement of supervision given to consumer protection regarding the online transportation sector. For this purpose, the legal research method is used with a discussion that is in line with consumer protection for online transportation. The results of the study were able to determine the form of legal protection and supporting factors in order to improve the enforcement of supervision in protecting consumers in the online transportation sector in Indonesia.